EVENT STUDY ON THE IMPACT OF THE COVID-19 OUTBREAK ON THE MALAYSIA STOCK MARKET RETURNS - Farah Hayati Binti Mustapa (Journal of Academia, 2022)
This study investigates the impact of the COVID-19 outbreak on the Malaysia stock market returns. We perform an event study to investigate the effect of the announcement of the coronavirus as a global pandemic, on the stock returns. The historical stock prices in each 30 components of KLCI were analysed. The results show that the Malaysia stock market is negatively impacted, i.e., the announcement of COVID-19 as a pandemic by WHO on 11th March 2020 has a significant effect on the Malaysia stock market returns. The study on the effect before and after the pandemic announcement also indicates that the event has significant effects on the stock price of Bursa Malaysia i.e., there is a negative sentiment that led to the decrease of the stock returns.